Review: Potensi Resin Kemenyan (Styrax benzoin) dan Senyawa Aktifnya Dalam Pengobatan Penyakit - Erlia Anggrainy Sianipar (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2023)
Studies on drug discovery from natural ingredients are important to determine the pharmacological effects of the compound’s content so that it can be used to treat diseases. Kemenyan (Styrax benzoin) resin has been widely used by the local community for various purposes, including medicine. This review article aims to provide a comprehensive view of the potency of Kemenyan resin and its active compounds so that they could be used and developed to treat diseases in the future. The method used was based on searching for scientific literature in national and international journals. The results showed that the Kemenyan resin contains active compounds, including cinnamic acid, benzoic acid, benzaldehyde, benzyl benzoate, vanillin, styrene, styracin, coniferyl benzoate, benziresinol resin, resinotannol, sterols, phthalic acid, and sumaresorcinol. These compounds are known to have various pharmacological effects, including antibacterial, anesthetic, anti-inflammatory, antispasmodic, antimutagenic, fungicidal, herbicidal, tyrosinase inhibitory, and LDL synthesis inhibitory effects. Based on these studies, it can be concluded that the Kemenyan resin has great potential for the treatment of various diseases.